Application of the anaerobic co-digestion method to sewage sludge treatment toward recover green energy and utilize nutrients for agriculture. Issue 1 (November 2021) - Tran, T; Hong, L T A; Tan, L V
Abstract: Sewage sludge after urban wastewater treatment needs to be treated intelligently to get maximum benefits. This study proposes a method of anaerobic co-degradation of agricultural sludge and residues to both solve environmental problems and recover a large amount of biogas and organic fertilizers. The results show the potential for energy recovery from biogas and impact assessment of the application directly on the rice fields. It is estimated that biogas recovery from sludge treatment from wastewater treatment plants gives a calorific value of about 76 × 106 MJ/year. Results from the trial crop showed that fertilizer shows good supportability to the plant. The results show that the fertilizer from sewage sludge can be reduced and replaced by 50% to 100% of the number of chemical fertilizers but still give the same yield. The data show that the anaerobic co-digestion method is a suitable method for sludge treatment. The dual objective is to provide valuable benefits from recovered biogas and anaerobic digestion products.